Five-year Follow-up Outcome of Total Omental Lymph Node Flap Transfer in Primary Lymphedema Patient - Nutcha Yodrabum, MD; Nattanit Poungjantaradej, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Lymphedemas are caused by the accumulation of protein-rich fluid in the interstitial space, resulting from lymphatic system obstruction. In recent years, omentum flap transfer has gained popularity as a treatment for lymphedema due to its immunogenic and lymphangiogenic properties, which aid in reducing infection rate and volume. Moreover, omental flaps have angiogenesis capabilities, which can aid in successful chronic wound covering. Using a flow-through procedure after omental flap transfer can help reduce complications including venous congestion and steal phenomenon at the recipient site. We present a long-term follow-up of a case of primary lymphedema treated with omental flap transfer with flow-through figuration, demonstrating a gradual decrease in volume, reduced infection rate, and chronic wound coverage. This case report illustrates intriguing postoperative compartment effect and vascular concerns.